2010
DOI: 10.1542/peds.2009-3225
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in Children and Young Adults Conceived by In Vitro Fertilization

Abstract: WHAT'S KNOWN ON THIS SUBJECT:No clear-cut increase in cancer risk after IVF has been found, but most studies were too small to answer the question. There are characteristics of children who are conceived by IVF that could increase cancer risk. WHAT THIS STUDY ADDS:This study is large enough to demonstrate that a slight but statistically significant cancer risk exists for children who are conceived by IVF. An interesting finding is the seeming increase in the risk for histiocytosis. abstract OBJECTIVES: Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
2
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 34 publications
5
74
2
12
Order By: Relevance
“…Increased risk of leukemia was observed with 3.8 years earlier in IVF offspring than in the control (OR 2.21, 95% CI 1.27-3.85) (Petridou et al, 2012). Meanwhile, a moderately increased risk of cancer in IVF children (RR 1.42, 95% CI 1.09-1.87) has also been observed by Källén B. et al (2010a) through a follow-up study of 26 692 children who were born after ART between 1982 and2005. In brief, the evidence of cancer risk in children after ART is still very limited. Further studies and long-term follow-up are necessary to determine whether ART had an impact on cancer occurrence.…”
Section: Risk For Cancermentioning
confidence: 89%
“…Increased risk of leukemia was observed with 3.8 years earlier in IVF offspring than in the control (OR 2.21, 95% CI 1.27-3.85) (Petridou et al, 2012). Meanwhile, a moderately increased risk of cancer in IVF children (RR 1.42, 95% CI 1.09-1.87) has also been observed by Källén B. et al (2010a) through a follow-up study of 26 692 children who were born after ART between 1982 and2005. In brief, the evidence of cancer risk in children after ART is still very limited. Further studies and long-term follow-up are necessary to determine whether ART had an impact on cancer occurrence.…”
Section: Risk For Cancermentioning
confidence: 89%
“…13 Nevertheless, few studies have reported the incidence of cancer in the already large and growing population of children born after fertility treatment and the results are inconsistent. While some studies showed increased risks for all cancers 14 and for specific types of cancer, such as retinoblastoma, 15 neuroblastoma, 6 leukemia, [16][17][18] and hepatoblastoma, 19,20 others found no association. [21][22][23][24][25][26][27][28][29][30][31][32] However, the main part of these studies are characterized by small sample sizes, short follow-up periods and lack of information on the use of fertility drugs.…”
mentioning
confidence: 99%
“…Källén et al, reported an increased rate of diagnosed histiocytosis in children conceived by means of in vitro fertilization, 6 cases of Langerhans histiocytosis against 1.0 expected [9]. Eosinophilic granuloma is the most common form of LCH, and usually presents as a solitary osteolytic lesion of the skull or spine.…”
Section: Discussionmentioning
confidence: 99%